Towards the design of drugs against the dengue virus RNA dependent RNA polymerase : mechanistic studies of enzyme activities and substrate binding. - Koh, Jolene Hong Kiew. (2012)
Dengue NS5 consists of 2 domains- methyltransferase and RNA-dependent RNA polymerase (RdRp), interspersed by a 9 amino acid linker. Currently, the full-length (FL) NS5 has not been structurally determined due to the flexibility of this linker, impeding drug discovery efforts. Here, FL NS5 with alanine mutation and RdRp domain with variable N-terminal extension (NE-RdRp) were expressed. The ability of these proteins to carry out de novo initiation (dnI) and elongation were then examined. Results showed decreased enzymatic activities for FL Glu271Ala, Pro273Ala and Lys272Ala proteins, while FL Thr270Ala, Ser265Ala and Glu269Ala proteins displayed increased dnI activity but no change in elongation activity. NE-RdRp domain proteins generally demonstrated increased activity compared to D274 NE-RdRp domain protein and more remarkably, greater enhancement for longer proteins. These combined findings suggest Glu271, Lys272 and Pro273 residues play a critical role in maintaining orientation between the two domains, while Glu269, Thr270 and Ser265 residues are important for local protein folding. Also, it indicates that the linker plays an important role in modulating polymerase activity. With these, a “lever” model was proposed for the linker region. Together, this pioneer study provides valuable insight on the biological function of the linker and information for rational drug design.